2019
DOI: 10.15666/aeer/1701_395408
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Environmental Factors on Aspergillus Niger Granite Weathering

Abstract: In order to explore the effects and influence of environmental factors on microbial restoration of waste rock, an efficient rock-weathering strain Aspergillus niger XF-1 was isolated from a granite face. Concentrations of SiO2 in nutrient solution at different temperatures, pH values, generation cycles, and vaccination quantities were measured using shake flask leaching and inductively coupled plasma optical emission spectrometer (ICP-OES) to analyze the grey correlation degree of weathering. The results revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Silicon (Si) in silicon dioxide (SiO2) is not available. Silicon decomposer microorganisms such as Aspergillus niger must be added to the soil solution, and Orthõsilicate acid is a form of silicon (Si) that is available and absorbed by plants [6]. Aspergillus niger can secrete oxalic acid, tartaric acid and citric acid to promote plant growth [7].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon (Si) in silicon dioxide (SiO2) is not available. Silicon decomposer microorganisms such as Aspergillus niger must be added to the soil solution, and Orthõsilicate acid is a form of silicon (Si) that is available and absorbed by plants [6]. Aspergillus niger can secrete oxalic acid, tartaric acid and citric acid to promote plant growth [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hall believes that in the environment with biological existence, biological weathering rocks can play a leading role under certain conditions (Hall et al, 2005 affect the weathering of rocks and minerals and promote the formation of soil through growth and reproduction and the formation of biofilms (Ehrlich, 1999). Researches showed that the main microorganisms weathering the rock minerals were B. mucilaginosus (Zeng, 2016), Burkolderia solanacearum (Barker, 1998), Pseudomonas protegens (Wu et al, 2017a;Wu, 2016), Bacillus megatherium (Wu et al, 2017b), Aspergillus niger (Wu, , 2019, Rhizobium tropici (Wang et al, 2015), Penicillium oxalicum (Song et al, 2015) and so on. The weathering effects of these microorganisms on mineral rocks include direct dissolution and mechanical damage, and indirect chemical corrosion.…”
Section: Introductionmentioning
confidence: 99%